2010
DOI: 10.5194/angeo-28-61-2010
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric composition forecasting in Europe

Abstract: Abstract.The atmospheric composition is a societal issue and, following new European directives, its forecast is now recommended to quantify the air quality. It concerns both gaseous and particles species, identified as potential problems for health. In Europe, numerical systems providing daily air quality forecasts are numerous and, mostly, operated by universities. Following recent European research projects (GEMS, PROMOTE), an organization of the air quality forecast is currently under development. But for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 96 publications
3
62
0
1
Order By: Relevance
“…Improving the performance of high-resolution localscale models requires high quality emission inventories with sufficiently high spatial resolution (Skjøth et al, 2011). In addition, a high temporal resolution for emissions is also crucial for the performance of CTMs, and dynamic calculations of NH 3 emissions are needed for a better prediction of high particulate matter episodes (Menut and Bessagnet, 2010;Henze et al, 2009). This is especially relevant as NH 3 emissions in winter will lead to a higher contribution to particulate matter than NH 3 emissions in summer.…”
Section: Improved Treatment Of Sub-grid Variability and Spatial And Tmentioning
confidence: 99%
“…Improving the performance of high-resolution localscale models requires high quality emission inventories with sufficiently high spatial resolution (Skjøth et al, 2011). In addition, a high temporal resolution for emissions is also crucial for the performance of CTMs, and dynamic calculations of NH 3 emissions are needed for a better prediction of high particulate matter episodes (Menut and Bessagnet, 2010;Henze et al, 2009). This is especially relevant as NH 3 emissions in winter will lead to a higher contribution to particulate matter than NH 3 emissions in summer.…”
Section: Improved Treatment Of Sub-grid Variability and Spatial And Tmentioning
confidence: 99%
“…To date, a total of 23 model systems routinely simulate the air quality over Europe, with seven systems also operated in the forecasting mode (Menut and Bessagnet, 2010). Due to the episodic nature of dust outbreaks, the representation of these events cannot be well simulated with solely the information of aerosol boundary conditions (Jiménez-Guerrero et al, 2008a;Menut and Bessagnet, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the episodic nature of dust outbreaks, the representation of these events cannot be well simulated with solely the information of aerosol boundary conditions (Jiménez-Guerrero et al, 2008a;Menut and Bessagnet, 2010). Vautard et al (2005a) showed that simulated aerosol loadings, using the current knowledge on aerosol mechanisms, may be underestimated by up to 30-50 % if only anthropogenic sources are taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…For a review of the current systems that provide aerosol forecasts, some with focus on dust, see for example Benedetti et al (2014) and Sessions et al (2015).Ensemble systems are presented in Rubin et al (2016) andDi Tomaso et al (2017). An overview of regional 240 aerosol forecasting systems can be found in Menut and Bessagnet (2010); Kukkonen et al (2011);Zhang et al (2012a, b); Baklanov et al (2014).…”
Section: Aerosol Prediction Modelsmentioning
confidence: 99%